FESTIVAL OF FOLK SONGS AND INSTRUMENTS PECE ATANASOSKI IN THE CONTEMPORARY MACEDONIAN CULTURE - Natasha Didenko (Philological Studies, 2019)
The research is an attempt for first comprehensive presentation of the “International Festival of folk songs and instruments Pece Atanasoski“ and his role in the modern Macedonian culture. The history of this cultural manifestation will be proceeded through the memory and documentation fоr its development and activity, as an important part of the Macedonian cultural history.